Relevansi dan Tantangan Bangunan Pemikiran Kritis dan Pemecahan Masalah Pendidikan Islam dalam Mengembangkan Literasi Informasi dan Kesadaran global Abad 21 - Salim Ashar (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Throughout written history, starting from the plateau with its republic, critical thinking and problem solving are considered to be a 3rd century BC skill, today with technological advances marked by Artificial intelligence it still considers it to be 21st Century thinking or the main thought of the revolution Industry 4.0. the assumption that the emergence of digital technology requires fundamental changes to the curriculum and to the teaching and learning approach to educating "digital native" or "network generation" generations. There is emptiness in this context so the building of critical thinking and 21st century skills is inadequate, even in combination. The presence of superior character or character must be specially prepared in the 21st century with respect to digital skills. The purpose of this paper is to describe the Relevance and Challenges of Building Critical Thinking and Problem Solving Islamic Education in Developing Information Literacy and Global Awareness in the 21st Century. From the discussion it concludes: 1) Business people, politicians, and educators unite around the idea that students need "century skills" 21st "to be successful today by ignoring morals or characters whose temptations are heavier than before. 2) the challenges of Islamic education in the post-modern world (21st century) various contradictions about the definition of moral acts that abound and change the idea of ??a good life, the philosophical foundation of the instrumental and normative pillars continue to erode, here Islamic Education must be present and play its role . 3) The effectiveness of Islamic education teachers individually being the main focus of school improvement over the past decade, the success of teachers in improving the quality of learning also affects the success of students as adults, is more likely to go on to college, have better jobs and have superior character called morals noble.